Manâfidu al-Muharramât ilâ Muntijâti al-Halâl: “Dirâsah Tahlîliyah fî Dhaw’i Ma’âyir Majma’ al-Fiqh al-Islâmî al-Dawlî wa al-Ma’âyir al-Mâlayziah” - Ahmed Salem; Muhammad Taufiq (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
This paper examines the changing process of unlawful (haram) materials into a lawful (halal) product according to both International Islamic Fiqh Academy standard and Malaysian standard. To harmonize those two halal standards on certain products, the subdiscipline of fiqh which determines lawful product standardization has put some fundamental sharia laws to clearly distinguish between halal and haram. The changing process is based on so called istihalah, referring to the merge among halal and haram and istihlak or possibility to take rukhshah (legal relief) and easiness to cope with any difficult condition using darurat (emergency causes) and umum al-balwa (common disaster). However, critical points of the standardization method need to well described, mainly on its composition based on shariah rules of halal product. The discussion covers difference opinions on the sharia law to the weak political policy on the Islamic law arrangement for halal product standardization that it is recommended to consider clear and more careful concepts (instead of istihalah, istihlak, darurat and umum al-balwa) in formulating the law.